Protocol for an HTA report: Does therapeutic writing help people with long-term conditions? Systematic review, realist synthesis and economic modelling. Issue 2 (18th February 2014) - Meads, C; Nyssen, O P; Wong, G; Steed, L; Bourke, L; Ross, C A; Hayman, S; Field, V; Lord, J; Greenhalgh, T; Taylor, S J C
Abstract : Introduction: Long-term medical conditions (LTCs) cause reduced health-related quality of life and considerable health service expenditure. Writing therapy has potential to improve physical and mental health in people with LTCs, but its effectiveness is not established. This project aims to establish the clinical and cost-effectiveness of therapeutic writing in LTCs by systematic review and economic evaluation, and to evaluate context and mechanisms by which it might work, through realist synthesis. Methods: Included are any comparative study of therapeutic writing compared with no writing, waiting list, attention control or placebo writing in patients with any diagnosed LTCs that report at least one of the following: relevant clinical outcomes; quality of life; health service use; psychological, behavioural or social functioning; adherence or adverse events. Searches will be conducted in the main medical databases including MEDLINE, EMBASE, PsycINFO, The Cochrane Library and Science Citation Index. For the realist review, further purposive and iterative searches through snowballing techniques will be undertaken. Inclusions, data extraction and quality assessment will be in duplicate with disagreements resolved through discussion. Quality assessment will include using Grading of Recommendations Assessment, Development and Evaluation (GRADE) criteria. Data synthesis will be narrative and tabular with meta-analysis where appropriate. De novo economic modelling will be attempted in one clinical area if sufficient evidence is available and performed according to the National Institute for Health and Care Excellence (NICE) reference case.